Energy spectra of the Fibonacci superlattice based on the gapped Graphene - Korol, Anatoliy; Isai, Valeriy (My University, 2013)
Energetical spectra for the Fibonacci superlattice on the gapped grapheme are evaluated andanalyzed.
Keywords: spectra; Fibonacci; graphene; спектри; Фібоначчі; щільовий графен; спектры; Фибоначчи; щелевой графен; кафедра фізики та професійної безпеки